Critical Care Medicine and the Catholic Tradition: Reflections on the Consensus Statement - McKenny, Gerald P. (Christian bioethics, 2001)
Gerald P. Mckenny; Critical Care Medicine and the Catholic Tradition: Reflections on the Consensus Statement, Christian bioethics: Non-Ecumenical Studies in Med